2007
DOI: 10.1007/s00213-007-0862-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial deficits in a mouse model of Parkinson disease

Abstract: These results confirm that dopamine depletion is accompanied by cognitive deficits and demonstrate that striatal dopamine dysfunction is sufficient to induce spatial information processing deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 45 publications
9
42
4
Order By: Relevance
“…Our conclusions are consistent with observations from rodent models of PD, where lesioning of DA neurons in the SNc results in deficits of visuospatial function (24)(25)(26). However, these models make no distinction between loss of DA signaling versus loss of DA neurons and do not separate performance from cognitive deficits.…”
Section: Object Memory and Visuospatial Learning Are Partially Restorsupporting
confidence: 90%
See 1 more Smart Citation
“…Our conclusions are consistent with observations from rodent models of PD, where lesioning of DA neurons in the SNc results in deficits of visuospatial function (24)(25)(26). However, these models make no distinction between loss of DA signaling versus loss of DA neurons and do not separate performance from cognitive deficits.…”
Section: Object Memory and Visuospatial Learning Are Partially Restorsupporting
confidence: 90%
“…In accordance with these observations, data from rodent models of PD indicate that the dorsal striatum contributes to various forms of learning and memory (22)(23)(24)(25)(26).…”
supporting
confidence: 54%
“…Consistently, extensive DA lesions, obtained through either medial forebrain bundle or dorsal striatum 6-hydroxydopamine (6-OHDA) administrations, have been found to impair memory in the spatial version of the Morris water maze in rats (Miyoshi et al, 2002;Mura and Feldon, 2003;Whishaw and Dunnett, 1985). Furthermore, it has been recently shown that partial bilateral DA depletion of the dorsal striatum impairs spatial discrimination in the object-place association task in mice, and that this effect is specific for spatial information (De Leonibus et al, 2007), thus providing an useful animal model of cognitive deficit in the early stages of PD.…”
Section: Introductionmentioning
confidence: 81%
“…For the future it might be interesting to study whether the Cx30 Ϫ/Ϫ /Cx47 Ϫ/Ϫ and Cx30 Ϫ/Ϫ /Cx47 ϩ/Ϫ mice are impaired in the one-trial inhibitory avoidance task. This test is known to be less sensitive to motor impairments and has been used to demonstrate preserved learning and memory functions in a mouse model of Parkinson disease (De Leonibus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%